FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU VULVA HYGIENE PADA REMAJA PUTRI PANTI ASUHAN DI KECAMATAN TEMBALANG, KOTA SEMARANG - Fathin Humairoh; Syamsulhadi Budi Musthofa; Laksmono Widagdo (Jurnal Kesehatan Masyarakat (Undip), 2018)
Vulva hygiene behavior is an action of maintaining and cleansing the outer part of female reproductive organ. In August 2016, 52 adolescents in Semarang had infections of the reproductive organs (19% Candidiasis, 17% Herpes Simplex virus, 13% bacterial vaginitis, 12% gonorrhoe, 10% Condyloma acuminata, 8% AIDS, 5% NGU, 4% Chlamidya tracomatis, 4% Herpes genitalis, 4% Trichomonas urethralis, and 4% others). Orphanage as the social welfare institution is in charge of giving protection and service including reproduction health service. The purpose of this research was to analyze factors related to vulva hygiene behavior in teenage girl at the orphanages at Tembalang District. Quantitative research, cross sectional approach. Sampling technique was using random sampling with 116 respondents. Data was analyzed using univariate, bivariate with chi square statistical test with 95% significance and multivariate.The results showed that majority of respondents were 12-15 years old, came from orphaned family. The 27,6% respondents were having bad vulva hygiene behavior. Chi square test results showed that knowledge about vulva hygiene (p=0,003) and friends support (p=0,01) were significantly correlated with vulva hygiene behavior. While age (p=0,8), early puberty age (p=0,179), education (p=0,297), background (p=0,966), attitude (p=0,087), availability of facility (p=0,058) and caregiver support (p=0,358) were not significantly correlated with vulva hygiene behavior. Regression binary logistic test result showed that from all variables, only knowledge about vulva hygiene was significantly influenced with vulva hygiene behavior (OR= 3,061). It was suggested for the orphanages to enhance the concern and guidance about vulva hygiene particularly in giving information and supporting facilities related to health and hygiene of reproductive organ.